Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00705-014-2292-z
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and phylogenetic analysis identifies candidate members of a new picornavirus genus in terrestrial tortoise species

Abstract: Near-complete genome sequences of seven picornavirus (PV) strains isolated from different terrestrial tortoise species were determined and characterized. The genome organization of the strains proved to be similar and displayed a typical PV layout, and the polyprotein-encoding regions showed low similarity to those of other PVs. The predicted regions of the tortoise PV genomes were related to the corresponding genome parts of viruses belonging to distinct genera, implying modular evolution of these novel virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The genome sequences of both tortoise picornavirus 1 and topivirus clustered with members of the genus Cardiovirus and related genera in cluster 2 [1, 10], while the ToRaV-A genome described here clustered with members of the genus Kobuvirus and related genera in cluster 3 (Fig. 1).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The genome sequences of both tortoise picornavirus 1 and topivirus clustered with members of the genus Cardiovirus and related genera in cluster 2 [1, 10], while the ToRaV-A genome described here clustered with members of the genus Kobuvirus and related genera in cluster 3 (Fig. 1).…”
mentioning
confidence: 98%
“…In both sequence and phylogenetic analysis, ToRaV-A is distinct from A) a recently reported picornavirus-like virus in juvenile tortoises (tortoise picornavirus 1 in Testudo graeca and Geochelone elegans ) [6] (Nick Knowles, unpublished data) and B) the recently described topivirus from Testudo graeca , Geochelone sulcata , and Pyxis arachnoides tortoises [1] (Neither sequence was publically available at the time of writing.) The genome sequences of both tortoise picornavirus 1 and topivirus clustered with members of the genus Cardiovirus and related genera in cluster 2 [1, 10], while the ToRaV-A genome described here clustered with members of the genus Kobuvirus and related genera in cluster 3 (Fig.…”
mentioning
confidence: 99%
“…PVs infect humans, several orders of mammals and birds, and have been reported in lower vertebrates including reptiles and fish. 2,5,6,10,13,15 With some exceptions, PVs cause mild or subclinical infections and are strictly host specific, inducing disease only in a single or a few closely related host species. 9 Picornaviruses of tortoises have been detected in several instances by virus isolation in Terrapene carolina heart cells (TH-1; ATCC CCL-50) based on their typical lytic cytopathogenic effect.…”
mentioning
confidence: 99%
“…The near complete genome sequences of a dozen tortoise PV strains have been determined and characterized. 5 Sequence analyses of these genomes showed that tortoise PVs do not belong to any recognized genera, but most probably are the first members of a new genus in the Picornaviridae family, provisionally named Topivirus. 5 Another group of tortoise PVs, rafivirus A was described in 2015 in Sulawesi tortoises (syn.…”
mentioning
confidence: 99%
See 1 more Smart Citation